2016
DOI: 10.17511/ijmrr.2016.i09.06
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Pancytopenia

Abstract: Introduction: Pancytopenia is a common and alarming condition encountered by clinicians. We had studied the clinical presentation, laboratory investigations and various etiologies of Pancytopenia. Material and Methods: Study was carried out in a tertiary care centre in western India. A total of 102 patients fulfilling the criteria of pancytopenia were enrolled and studied. Results and conclusion: Megaloblastic anemia was commonest cause of pancytopenia. Easy fatigability and pallor were commonest symptoms and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…12 Also similar study carried out by Vaidya et al found the most common age group was 21-30 years comprising 33.24 % of cases. 13 Similarly our results of age and sex ratio were comparable with other studies carried out by Thakkar et al, Manzoor et al, Yadav et al and Zeeshan et al [14][15][16][17] The study carried out by Lakhey et al in Nepal found weakness was the predominant presenting clinical feature in 73.9% cases. 18 Khodke et al studied 50 pancytopenia cases and found commonest presenting complaint was fever (40%) followed by weakness (30%) and bleeding manifestations (20%).…”
Section: Discussionsupporting
confidence: 91%
“…12 Also similar study carried out by Vaidya et al found the most common age group was 21-30 years comprising 33.24 % of cases. 13 Similarly our results of age and sex ratio were comparable with other studies carried out by Thakkar et al, Manzoor et al, Yadav et al and Zeeshan et al [14][15][16][17] The study carried out by Lakhey et al in Nepal found weakness was the predominant presenting clinical feature in 73.9% cases. 18 Khodke et al studied 50 pancytopenia cases and found commonest presenting complaint was fever (40%) followed by weakness (30%) and bleeding manifestations (20%).…”
Section: Discussionsupporting
confidence: 91%